A new strategy for achieving white-light emission of lanthanide complexes: effective control of energy transfer from blue-emissive fluorophore to Eu(iii) centres1. Issue 8 (28th February 2015) - Zhang, Junqing; Li, Hongfeng; Chen, Peng; Sun, Wenbin; Gao, Ting; Yan, Pengfei
<x xml:space="preserve">Abstract</x> A white-light-emitting Eu(iii) coordination polymer based on a 1, 8-naphthalimide-derivative was synthesized, and three primary colours are well balanced by controlling energy transfer efficiency from fluorophore to Eu(iii) ions.